The Effect of Avocado Leaf Decoction on Lowering Blood Pressure in Elderly People with Hypertension in Mongolato Village - Andi Nur Aina Sudirman; Rona Febriyona; Nova Rahmawati Kamali (PROMOTOR, 2023)
Hypertension is a condition where there is an increase in blood pressure that can affect the function of other organs, such as the heart and kidneys, and even cause death. The purpose of this study was to analyze the effect of avocado leaf decoction on the elderly. This type of research is quantitative research using a quasi-experimental two-group pretest – post-test research design with a control design. The sample size of 20 respondents consisted of 10 experimental groups and 10 control group respondents determined by purposive sampling techniques. The research instruments used are a sphygmomanometer and stethoscope, observation sheet, food recall sheet, and SOP. The statistical test used is the paired t-test. The results showed a decrease in blood pressure in the intervention group with P value = 0.000 in systolic and diastolic blood pressure which means there was a decrease in blood pressure. The experimental group was given a decoction of avocado leaves 1 time a day for 5 days in the morning. It can be concluded that there is an effect of avocado leaf decoction on lowering blood pressure. It is recommended that people plant avocado trees so that the leaves can be used as traditional medicine to lower blood pressure. And the fruit can be used for other needs.